Measurement properties of the Chinese version of the Mental Fatigue Scale for patients with traumatic brain injury. (16th April 2018) - Chiu, Hsiao-Yean; Li, Wei; Lin, Jiann-Her; Su, Yu-Kai; Lin, En-Yuan; Tsai, Pei-Shan
ABSTRACT: Objectives : To translate the Mental Fatigue Scale into a Chinese version (CMFS), to develop a more valid and precise CMFS by using an item response theory-based model, and to examine the reliability and validity of the CMFS. Methods : One hundred and fifty adults having traumatic brain injury for at least 6 months were included. Each participant completed a battery of questionnaires (i.e. the Chinese version of the Chalder Fatigue Scale [ChCFS], Chinese version of the Clinically Useful Depression Outcome Scale [CUDOS-Chinese], and CMFS). Two-parameter graded response models were used to evaluate the location and discrimination performance of the CMFS. The reliability and validity of the CMFS were also evaluated. Results : One item investigating 'increased sleep at night' (item 14) was removed because it had a low discrimination value (0.86) and provided less information. The internal consistency and test–retest reliability of the 13-item CMFS were high (0.92 and 0.96, respectively). The CMFS score was positively correlated with the ChCFS and the CUDOS-Chinese scores ( r  = 0.77 and 0.80, respectively). Conclusion : The CMFS provides reliable and valid information on mental fatigue for future research and clinical practice involving patients with traumatic brain injury.